Strategies to Uphold Food Sovereignty In Indonesia: Strategi Menegakkan Kedaulatan Pangan di Indonesia - Sadarestuwati, Sadarestuwati; Suryaningsih, Dwi Retna; Haryanta, Dwi (Journal of Applied Plant Technology, 2023)
The principle of food sovereignty is a democratized system of food, transparent, environment-based, local products and markets as the main pillars in achieving sustainable food security. Food sovereignty makes a very real contribution to overcoming food insecurity in areas where there are frequent extreme climates, crop failures, dependence on imported food, and encouraging the provision of long-term healthy food (sustainable) that is accessible to all communities (equitable) and encourages local food production and consumption (local wisdom). Food sovereignty seeks to improve the quality of life of farmers and rural communities. Strategies to build food sovereignty can be through (a) Utilization of biodiversity as a sustainable source of food through diversification of local food, (b) Improvement of agricultural cultivation and quality of food production through research and innovation produced by BRIN, (c) Consistency in the implementation of protection of productive agricultural lands from land use conversion, (d) Support for monetary, fiscal policies and access to finance for farmers, fishermen, and other food producers, (e) Improving the technology of processing/downstreaming food commodities in a productive, efficient, competitive, and sustainable manner, (f) Development of infrastructure and food production facilities appropriately and integrated, (g) Synergy of food development policies between the central and regional governments, and (h) Implementation of import duties on food imports to protect domestic food commodities and products.